Eksistensi Pesantren Sebagai Pusat Pendidikan Dan Perubahan Masyarakat Bangsa Indonesia Di Abad Ke-19 Dan Abad Ke-20 - Muh. Mustakim (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2016)
This article discusses the sustainability of pesantren in Indonesia, especially in the 19th century and the 20th century . In the century, the pesantren was instrumental in educating the children of the nation, became the center of civilization Indonesia even become the biggest supplier in guarding the struggle against colonialism struggle, safeguard and defend freedom of Indonesia. The major role as faded in the era of the 21st century, where schools are more focused on religious education . Some schools try to maintain the existence and role by accepting changes to the education system or the management pesantrennya that survive today, such as the opening of school education as madrassah, or boarding schooland college or university, par example as done by many pesantren in East Java, Central Java and Yogyakarta and other areas in Indonesia